EL EJERCICIO DE LA CIUDADANÍA EN LA ERA DEL CAPITALISMO ELECTRÓNICO - Alencar, Breno Rodrigo de Oliveira (2024)
This review deals with the book "Citizens Replaced by Algorithms" by Néstor García Canclini, whose aim is to demonstrate that, in the current state of affairs, the use of social networks en masse, with awareness and political engagement, functions as a new way of exercising citizenship. Throughout the book, the author discusses how mobilization through networks has already led to important revolutionary clashes in this century. In this way, the book presents a very positive perspective on the use of technology, which is even capable of shaping new forms of social participation that go beyond party mobilization.